Incremental returns from rice cultivation through gender sensitive approaches - a vivid illustration - Das, Lipi; Mondal, Biswajit; Mishra, S K; Sadangi, B N (ORYZA-An International Journal of Rice, 2021)
In addition to several household chores, women in rural areas remain involved very actively in farming activities.Â On getting similar access to productive resources as men, women can boost overall agricultural output as well as income significantly. A group of farm women from ’Sankilo’ village of Cuttack district, Odisha have beenÂ provided with half-an acre land with the power to decide all farm operations and ICAR-NRRI, Cuttack providedÂ technical support for five years’ period. It is being observed that returns from rice cultivation increasedÂ considerably and ’technology’ in terms of demonstrations mostly contributed the difference in yield and returnsÂ over pre-project situations. Household income of family of individual women was also assessed and observedÂ that education, family size and irrigated land holding determine the variations in income. The study advocatedÂ for appropriate policies to extend access of farm resources and impart proper education as well as capacity building of the women for enhancing the knowledge and adoptive capacity for the technologies to boost theÂ yield and income.